Enhancing network lifetime with an improved MOD- LEACH - Brijesh Kundaliya; S.K. Hadia (Institute of Advanced Engineering and Science, 2019)
Wireless sensor network will be the most dominating field in future era. There are certain issues which wireless sensor network suffers from. The main concern with wireless sensor network is limited energy which directly impact on network lifetime. In this paper we modify the cluster selection procedure of MODLEACH. MODLEACH protocol use threshold value for selecting cluster head. Once a cluster head is selected, it retains its position until it bypasses the threshold limit. In Basic LEACH, it does not use any threshold value but it randomly selects cluster head from the available nodes. We combine the probabilistic nature of LEACH to select the cluster head and threshold base selection of cluster head of MODLEACH. We also apply proposed modification in EAMMH protocol. Our main focus is on the enhancement of network lifetime, and we got significant improvement in network lifetime.